Comportamento a fatica dei giunti saldati in funzione della densità di energia di deformazione locale: influenza dei campi di tensione singolari e non singolari - Paolo Lazzarin (Fracture and Structural Integrity)
In the Strain Energy Density (SED) approach for fatigue strength assessments of welded joints a well-defined control volume is considered. This volume surrounds the weld root or weld toe, both modelled like sharp (zero radius) V-notches with different opening angles. The volume becomes a circular sector under plane strain conditions, with the radius being about 0.3 mm for welded joints made of structural steel. The mean value of the SED mainly depends on the singular stress fields when the main plate thickness is large enough, whereas the influence of the T-stress component cannot be neglected in the case of thin-walled welded joints. Both contributions are directly accounted for by using finite element models, also when the relevant meshes are quite coarse. This fact makes the application of the SED approach easier than any stress-based approach in the case of complex structures. Due to three-dimensional effects, a non conventional out-of-plane singular mode can be present, in addition with respect to modes I and II of the Williams’ solution. This out-of-plane mode, analogous to the Mode III, is discussed here with reference to welded (seam) lap joints under tensile-shear loads.